Experiences Of Crime Amongst Youth From A Gender Perspective: A Preliminary Analysis - Endut, Noraida; Selamat, Nor Hafizah; Abdul Kuthoos, Haja Mydin; Azmawati, Azman Azwan; Mohd Hashim, Intan Hashimah (Universiti Sains Malaysia, 2016)

(untitled)
Crime index in Malaysia has increased significantly over the years. There is an emerging trend today of juvenile involvement in crime and other social ills. Juvenile crime involving children aged 12 to 17 years experiences a 47% increment. There is also a notable increase of female juveniles in Malaysia. This paper contributes to the understandings of factors motivating criminal behaviour amongst youths by making a preliminary analysis of male and female juveniles’ experiences in Malaysia. Face to face indepth interviews were applied in the study that becomes the basis of this paper. The participants were residents of two rehabilitative facilities for juveniles in the Penang and Kedah, two northern states of Malaysia. This study of 37 male and 19 female juvenile offenders find that there are noteworthy gender differences in the whole experiences of serving incarceration at their respective schools. Preliminary analysis indicated several gender differences of male and female in overall referral rates to juvenile court, type of crime they committed, and level of violent offences. From the interviews, the study preliminarily finds that common narratives demonstrate male and female similarities in terms of factors leading them to the commission of crime. Female offenders, like male offenders tend to come from background marked by disadvantaged economic conditions, poor schooling and lack of attention from parents and/ or guardians. However, boys and girls may articulate their contexts of existing and desired support in different manners. This preliminary analysis can be the basis for rethinking further data gathering on juvenile delinquency issues and further strategies for intervention that may help rebuild juveniles’ senses wellbeing.